Improving Emergency Department Patient Experience Through Implementation of an Informational Pamphlet. (April 2020) - Sangal, Rohit B; Orloski, Clinton J; Shofer, Frances S; Mills, Angela M
Objective: Patient satisfaction is emerging as a new health-care metric. We hypothesized that an emergency department (ED) informational pamphlet would significantly improve patient understanding of ED operations and ultimately improve patient satisfaction. Methods: We performed a prospective study of patients presenting to a single tertiary care center ED from April to July 2017. All patients were given a pamphlet on alternating weeks with regular care on opposite weeks and were surveyed upon ED discharge. The primary outcome was patient satisfaction with ED care. Secondary outcomes included patient understanding of various wait times (test results, consultants), discharge process, who was on the care team and what to expect during the ED visit. Results: Four hundred ninety-four patients were included in this study and 266 (54%) were in the control group. Of 228 (46%) patients who were given the pamphlet, 116 (51%) were unaware they received it. Of the remaining 112 (49%) patients who remembered receiving the pamphlet, 43 (38%) stated they read it. Among those reading the pamphlet, only two statements were significant: knowing what to expect during the ED visit (88% vs 71%; P = 0.012) and waiting time for test results (95% vs 75%; P = 0.003) when compared to those who did not receive or read the pamphlet. Conclusion: An ED informational pamphlet, when utilized by patients, does improve patient understanding of some aspects of the ED visit but does not appear to be the best tool to convey all information. Ultimately, sustained improvement in patient satisfaction is a complex and dynamic issue necessitating a multifactorial approach and other methods should be explored.